Vietnamese Speech Act Realization and Some Factors Influencing Refusal Strategies: A Pilot Study - Bui, Tuyen (International Journal of Language and Literary Studies, 2024)
The purpose of this pilot research was to explore the refusal strategies and factors influencing speech act realization of refusals employed by a group of Vietnamese language learners when making refusals to invitations, requests, offers, and suggestions by 5 participants at Tien Giang University to shed light on the possible problems leading to cross-cultural differences in communication. A Written Discourse Completion Test (WDCT) and 5 interview questions in English versions developed by the researcher were used to collect the data and analyze it qualitatively and quantitatively. The results illustrated that the participants frequently used indirect strategies for refusing each context given in the WDCT. Furthermore, based on the participants’ answers via the interview records, it could be concluded that social contexts, distance, and cross-cultural differences influenced L2 learners of English as a Foreign Language. The findings of this study highlight some strategies to help learners understand and gain more strategies in speech act realization of refusals and misunderstanding can be avoided. Besides, the interlocutors can receive appropriate responses to refusing invitations, requests, offers, and suggestions.